Author Correction: The digital scribe. Issue 1 (December 2018) - Coiera, Enrico; Kocaballi, Baki; Halamka, John; Laranjo, Liliana
The original version of the published Article contained an error in the spelling of the third Author's name. "John Halamaka" has been changed to "John Halamka". This has been corrected in the HTML and PDF version of the Article.